2003
DOI: 10.1161/01.hyp.0000094221.86888.ae
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weight Reduction on Blood Pressure

Abstract: Abstract-Increased body weight is a strong risk factor for hypertension. A meta-analysis of randomized controlled trials was performed to estimate the effect of weight reduction on blood pressure overall and in population subgroups. 2 ) for American adults aged 20 to 74 years increased from 13.4% to 30.9%. In 2000, the prevalence of overweight (BMI Ն25 kg/m 2 ) for American adults was 64.5%. 3 Weight loss has been proposed as an effective, nonpharmacologic means for the primary prevention of hypertension. 4 An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
321
4
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,091 publications
(382 citation statements)
references
References 39 publications
22
321
4
15
Order By: Relevance
“…However, the results are comparable to analyses which showed, for each kilogram of weight loss, that systolic and diastolic blood pressures fall by 1?0 mmHg each (47) and blood parameters improve: total cholesterol by 20?13 mmol/l, TAG by 20?09 mmol/l, LDL cholesterol by 20?05 mmol/l, HDL cholesterol by 10?004 mmol/l (48) and fasting plasma glucose by 20?2 mmol/l (49) .…”
Section: Discussionsupporting
confidence: 76%
“…However, the results are comparable to analyses which showed, for each kilogram of weight loss, that systolic and diastolic blood pressures fall by 1?0 mmHg each (47) and blood parameters improve: total cholesterol by 20?13 mmol/l, TAG by 20?09 mmol/l, LDL cholesterol by 20?05 mmol/l, HDL cholesterol by 10?004 mmol/l (48) and fasting plasma glucose by 20?2 mmol/l (49) .…”
Section: Discussionsupporting
confidence: 76%
“…6 The BP was higher in men. Eison et al 14 found a higher prevalence of hypertension in men during 24 h ABPM in a small group of non-obese patients with mild and untreated hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…4 The Framingham Heart Study suggests that 78% of hypertension in men and 65% in women can be directly ascribed to obesity, 5 and a meta-analysis of 25 randomized-controlled trials showed reductions in systolic and diastolic blood pressure (BP) of E1 mm Hg for each kilogram of weight loss. 6 Gender differences in hypertension have been well described. Thus, hypertension is more common in men before 59 years.…”
Section: Introductionmentioning
confidence: 99%
“…66 There was no weight-independent effect of rimonabant on BP and the degree of reduction was lower than that expected by the weight loss. 67 …”
Section: Mechanisms Of Obesity-induced Hypertension V Kotsis Et Almentioning
confidence: 99%